How Visitor and Environmental Characteristics Influence Perceived Crowding - Rasoolimanesh, Mostafa S.; Jaafar, Mastura; Marzuki, Azizan; Mohamad, Diana (Routledge, 2016)
This paper aims to investigate tourists’ perceptions of crowding and factors influencing those perceptions. The effects of visitor socio-demographic characteristics, economic factors, and destination situational characteristics are investigated. Questionnaire data were collected from a sample of 362 tourists at Pantai Cenang Beach, Langkawi Island. The results confirmed the significant effect of visitor socio-demographic characteristics on perceived crowding. Among the economic factors, although the findings did not confirm an effect for level of income, the results showed a positive effect for spending money per day on perceived crowding. Furthermore, the hypothesized effect of situational characteristics on perceived crowding could not be verified. In light of the absence of studies investigating the factors influencing perceived crowding using partial least squares–structural equation modeling, this study contributes theoretically and methodologically to the perceived crowding literature. Moreover, the results can assist the local authorities to understand the perceptions of tourists for future development.